The gender politics of domestic violence: feminists engaging the state in Central and Eastern Europe - Krizsán, Andrea (Gender and comparative politics, 2018)
Introduction: the gender politics of domestic violence policy reforms in Central and Eastern Europe -- Five stories of change -- Mapping gendered meanings of domestic violence legal and policy reforms: comparing policy change over time -- Politicizing domestic violence: dynamics of gendered structures -- Comparing women's movements across the region -- How does gender disappear and reappear in domestic violence policy regimes -- Conclusions: gendering domestic violence policies